2007
DOI: 10.1111/j.1474-8673.2007.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2‐ and P2Y4 purinergic receptors are over‐expressed in human colon cancer

Abstract: 1. A characteristic of cancer is altered signal transduction leading to uninhibited growth. Adenosine-5'-triphosphate (ATP), a natural ligand at P2X- and P2Y purinergic receptors may regulate cell growth in non-neoplastic, as well as neoplastic tissues. In the human colon cancer cell line, HT-29, we previously demonstrated the expression of purinergic receptors of the P2Y(2)- and P2Y(4) subclasses. 2. The aim of the current study was to investigate whether these two purinergic receptors are expressed also in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…P2X7 was slightly over-expressed in htCD39 liver metastases only. P2Y2 mRNA was significantly over-expressed in htCD39 mice, compared to wt and heterozygous samples and human colon cancer cells [24]. There remain controversies as to how P2Y2 might also positively influence tumor proliferation and bolster progression.…”
Section: Discussionmentioning
confidence: 99%
“…P2X7 was slightly over-expressed in htCD39 liver metastases only. P2Y2 mRNA was significantly over-expressed in htCD39 mice, compared to wt and heterozygous samples and human colon cancer cells [24]. There remain controversies as to how P2Y2 might also positively influence tumor proliferation and bolster progression.…”
Section: Discussionmentioning
confidence: 99%
“…The P2 receptors are divided into P2X and P2Y groups and each group contains several members with distinct ion selectivity and regulatory properties. Numerous studies have demonstrated that P2 receptors involve in cancer cells and are expressed to a very high level in some cases, such as P2X3, P2X5, P2X7 and P2Y2 and P2Y442, 80, 81, 82, 83 (Table 1). In terms of clinical evaluation, P2X3 receptor overexpression was reported to be associated with poor recurrence-free survival in hepatocellular carcinoma patients 84 .…”
Section: Altered Ca2+ Channels/transporters In Cancermentioning
confidence: 99%
“…In recent years, most studies have concentrated on the effect of purinergic signaling on the development and progress of tumors. It has been shown that the expression of P2Y receptors is up-regulated in some cancer tissues (6,7). Extracellular nucleotides regulate the proliferation of several cancer cell lines through P2Y receptors (8,9).…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%